2020
DOI: 10.1017/ice.2020.1236
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Clostridioides difficile colonization among hospitalized adults: A meta-analysis and systematic review

Abstract: Objective: To identify risk factors for asymptomatic Clostridioides difficile colonization among hospitalized adults utilizing a meta-analysis, which may enable early identification of colonized patients at risk of spreading C. difficile. Design: Meta-analysis and systematic review. Methods: We systematically searched MEDLINE, Scopus, Web of Science, and EMBASE from January 1, 1975, to February 15, 2020, for articles related to C. difficile colonization among hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…Indeed, asymptomatic C. difficile transmission has been posited as an explanation for the missing epidemiologic links in whole-genome sequencing studies (14). Asymptomatic C. difficile colonization among hospitalized patients is not uncommon (12,(17)(18)(19)(20). For example, a meta-analysis found that ≈10% of hospitalized patients in North America become colonized (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, asymptomatic C. difficile transmission has been posited as an explanation for the missing epidemiologic links in whole-genome sequencing studies (14). Asymptomatic C. difficile colonization among hospitalized patients is not uncommon (12,(17)(18)(19)(20). For example, a meta-analysis found that ≈10% of hospitalized patients in North America become colonized (20).…”
Section: Discussionmentioning
confidence: 99%
“…Aaron C. Miller, Alan T. Arakkal, Daniel K. Sewell, Alberto M. Segre, Sriram V. Pemmaraju, Philip M. Polgreen; CDC MInD-Healthcare Group C. difficile after discharge (17)(18)(19)(20), this patient population could represent a large reservoir of CDI outside healthcare settings.…”
Section: Risk For Asymptomatic Household Transmission Of Clostridioid...mentioning
confidence: 99%
“…The use of corticosteroids increases the risk of C. difficile colonization in adults admitted to the hospital [ 14 ] and immunosuppressive therapy is a risk factor for complicated CDI [ 15 ]. Immunocompromised patients have a higher risk of developing rCDI during hospitalization [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent hospitalization or a recent intensive care unit stay increases the risk of developing CDI by 2.2 and 6.5, respectively [ 11 ]. Hospitalization in the previous 6 months increases the risk of colonization by 2.18 [ 14 ]. Previous studies showed that in an ambulatory group ( n = 43), in patients with short hospital stays ( n = 48) and in patients with long hospital stays ( n = 102), the percentages of C. difficile carriage were 9.5%, 8% and 13%, respectively [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another risk concerns antibiotic classes: late-generation cephalosporins and carbapenems present a higher risk [ 21 ], but even relatively narrow-spectrum antibiotics, such as ampicillin, are associated with CDI. A recent work by Anjewierden et al [ 22 ] has identified risks for asymptomatic CDI, such as hospitalization within six months prior to infection, nasogastric tube feeding, use of gastric acid suppression therapies, as well as use of corticosteroids in the previous eight weeks.…”
Section: Introductionmentioning
confidence: 99%